Defensive silence as a mediating variable Between Organizational Trust and Work Alienation: A Field Study on Aleppo Public Banking Sector - Alabed, Ayam Ibrhm (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed at identifying the effect of defensive silence on the relationship between organizational trust and work alienation among employees in all public banks in Aleppo at the significance level (α ≥ 0.05), And the disclosure of the impact of organizational trust with its dimensions (trust in the manager, trust in co-workers, trust in the organization) on work alienation with its dimensions (Powerlessness, Meaninglessness, Self-Estrangement). To achieve the objectives of the study, was used the descriptive analytical approach and reference to previous literature. A questionnaire as a tool for the study consisting of (47) items distributed on (7) areas: (defensive silence, trust in the manager, trust in co-workers, trust in the organization, Powerlessness, Meaninglessness and Self-Estrangement), and after verifying its validity and stability, it was applied to a sample of (270) male and female employees working in the public banking sector in Aleppo including( Central Bank, Real Estate Bank, Commercial Bank, Industrial Bank, Popular Credit Bank and Savings bank). The study found that there is significant effect of organizational confidence in work alienation. And the existence of a statistically significant effect of organizational confidence in defensive silence among workers in the government banking sector in the city of Aleppo at the significance level (α ≥ 0.05), as well as a significant effect of defensive silence on the relationship between organizational trust and work alienation at the significance level (α ≥ 0.05). The study recommended the necessity of encouraging employees to present creative ideas and reward them for that in order to compete among themselves to present the best ideas that contribute to the development of the work mechanism in banks and the need to provide an organizational climate that ensures the development of employees and the development of their skills and abilities in order to increase the sense of self-realization and affiliation in the banks which they work.
Keywords: Organizational Trust; Defensive Silence; Work Alienation; Powerlessness; Meaninglessness; Self-Estrangement